PENERAPAN E-COMMERCE DENGAN METODE CRM BERBASIS WEBSITE PADA TOKO BATAVIA COLLECTION - Mulyadi, Iriene Putri; Yaasin, Muhammad; Rahman, Fadil Aulia; Rifaldi, Dianda; Ramadhan, Fauzan Purma; Saputra, Vanji (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2026)
Website-based e-commerce is a crucial strategy for increasing transaction efficiency and fostering stronger relationships with customers, especially in the fashion sector. Among the fashion brands, Batavia Collection uses digital systems with Customer Relationship Management (CRM) integration to make it easier for customers to access product information, conduct online transactions, and communicate wirelessly with customers. The waterfall method is used to build the system, covering the phases of requirement analysis, system design, implementation, and pengujian. CRM integration is useful for managing customer data, supporting sales activities, and expanding personal services. According to the study's findings, operational efficiency has increased, customer satisfaction, and the potential for more extensive market expansion. This system also aids in more systematic promotion and pelaporan processes. The implementation of CRM-based e-commerce can increase Batavia Collection's sales and service quality.